Postoperative antibiotics and infection rates after implant-based breast reconstruction: A systematic review and meta-analysis - Hu, Yang; Zhou, Xuan; Tong, Xiaofei; Chen, Xiangyu; Wang, Mingzhu; Wu, Xianrui; Li, Peiting; Tang, Fengjie; Zhou, Jianda; Li, Ping (Frontiers in Surgery, 2022)
Purpose: Infection is the most common complication following breast implant surgery. Nevertheless, the systematic administration of antibiotics after breast implant surgery has been subjected to controversial debate. In this study, we sought to elucidate the association between infection and the use of antibiotics as an aftermath of breast implantation surgical procedures. Methods: Relevant studies were identified from PubMed, Web of Science, and EMBASE search mining. The extracted data included study type, basic characteristics, administrated antibiotic information, and clinical outcomes. Random-effects models were utilized to estimate outcomes, while study quality, statistical bias, and heterogeneity were also analyzed. Results: A total of 7 studies involving a total of 9147 subjects were included. The results demonstrated that the use of antibiotics after breast implantation reduced the incidence of infection (risk ratio [RR]: 0.65, 95% CI: 0.46-0.90). Nevertheless, smoking, obesity and diabetes type II are risk factors for postoperative infections. Sensitivity analysis verified the robustness of the results. Conclusions: Our study identified the administration of antibiotics after breast implantation as an intervention that decreased the incidence of infection. Smoking, obesity, and diabetes type II are risk factors for postoperative infections. These findings strongly suggest that timely and effective antibiotic interventions will be crucial in future clinical practice, which may reduce the risk of postoperative infection following breast implantation. Keywords: meta-analysis; postoperative antibiotics; infection; implant-based breast surgery; breast reconstruction